Decreased antithrombin activity and inflammation in cats. Issue 6 (June 2021) - Sun, Prudence; Jeffery, Unity
Objectives: The objective of this study was to determine if inflammatory markers are associated with antithrombin activity in cats. Methods: For a retrospective population of 231 cats admitted to a referral hospital, antithrombin activity was classified as decreased (n = 77), intermediate (n = 97) or in the upper quartile (n = 57). Odds ratios (ORs) were calculated for an association between decreased or upper quartile activity and hypoalbuminemia, hyperfibrinogenemia, band neutrophilia and toxic change. Multiple logistic regression was performed to determine if an association between band neutrophilia and decreased antithrombin activity was independent of decreased hepatic synthesis, consumptive coagulopathy or protein loss. Results: Cats with decreased antithrombin activity were more likely than cats with intermediate-to-upper quartile activity to have band neutrophilia (OR 2.85, P = 0.0050), hypoalbuminemia (OR 12.1, P <0.0001) or toxic neutrophils (OR 4.47, P <0.0001). Cats with antithrombin activity in the upper quartile were less likely than those with intermediate-to-low activity to have hypoalbuminemia (OR 0.31, P = 0.0023) or toxic neutrophils (OR 0.44, P = 0.033). In a regression model that included other mechanisms for decreased antithrombin, band neutrophilia remained associated with decreased antithrombin activity (adjusted OR 2.62, P = 0.013). Conclusions and relevance: Contrary to previous studies suggesting antithrombin is a feline positive acute phase protein, this study demonstrates an association between decreased antithrombin activity and inflammation. Further studies are needed to determine the mechanistic basis of this association.